Non-small-cell lung cancer: how to manage ALK-, ROS1- and NTRK-rearranged disease - Daniele Marinelli; Marco Siringo; Giulio Metro; Biagio Ricciuti; Alain J Gelibter (Drugs in Context, 2022)
Oncogene addiction in non-small-cell lung cancer (NSCLC) has profound diagnostic and therapeutic implications. ALK, ROS1 and NTRK rearrangements are found in about 2–7%, 1–2% and 0.2% of unselected NSCLC samples, respectively; however, their frequency is markedly higher in younger and never-smoker patients with adenocarcinoma histology. Moreover, ALK, ROS1 and NTRK rearrangements are often mutually exclusive with other known driver alterations in NSCLC. Due to such a low frequency, diagnostic screening with accurate and inexpensive techniques such as immunohistochemistry is useful to identify positive cases; however, confirmation with fluorescent in situ hybridization or next-generation sequencing is often required due to higher specificity. In ALK-rearranged NSCLC, sequential treatment with second-generation and third-generation tyrosine kinase inhibitors leads to long-lasting disease control with most patients surviving beyond 5 years with metastatic disease. In ROS1-rearranged NSCLC, first-line treatment with crizotinib or entrectinib and subsequent treatment with lorlatinib at disease progression leads to similar results in patients with metastatic disease. NTRK1–3 fusions are extremely rare in unselected NSCLC. However, treatment with TRK inhibitors yields high response rates and durable disease control in most patients; diagnostic screening through multigene DNA/ RNA-based next-generation sequencing testing is therefore crucial to identify positive cases.